2019
DOI: 10.1371/journal.ppat.1007887
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical NLRP3 inflammasome activation and IL-1β signaling are necessary to L. amazonensis control mediated by P2X7 receptor and leukotriene B4

Abstract: Leishmaniasis is a neglected tropical disease affecting millions of individuals worldwide. P2X7 receptor has been linked to the elimination of Leishmania amazonensis . Biological responses evoked by P2X7 receptor activation have been well-documented, including apoptosis, phagocytosis, cytokine release, such as IL-1β. It was demonstrated that NLRP3 inflammasome activation and IL-1β signaling participated in resistance against L . amazonensis .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 68 publications
3
35
0
3
Order By: Relevance
“…The protective role of caspase‐11 is also evident in BMDM, as Casp11 −/− BMDM failed to restrict L major , L braziliensis, and L amazonensis growth in vitro. Another study demonstrated a similar protective role for caspase‐11 following footpad injection with L amazonensis, where Casp11 −/− mice presented with significantly larger footpad lesions and higher parasite burden compared to WT mice 82 …”
Section: Consequences Of Nlrp3 Inflammasome Activation In Leishmaniasismentioning
confidence: 80%
See 4 more Smart Citations
“…The protective role of caspase‐11 is also evident in BMDM, as Casp11 −/− BMDM failed to restrict L major , L braziliensis, and L amazonensis growth in vitro. Another study demonstrated a similar protective role for caspase‐11 following footpad injection with L amazonensis, where Casp11 −/− mice presented with significantly larger footpad lesions and higher parasite burden compared to WT mice 82 …”
Section: Consequences Of Nlrp3 Inflammasome Activation In Leishmaniasismentioning
confidence: 80%
“…More recently, ATP‐induced leukotriene B4 (LTB4) has been suggested to activate caspase‐11‐mediated non‐canonical NLRP3 inflammasome during L amazonensis infection 82,83 (Figure 2). It should be noted, however, that Chaves et al used exogenous ATP or LTB4 during L amazonensis infection to activate the non‐canonical NLRP3 inflammasome 82 .…”
Section: Activation Of the Nlrp3 Inflammasome During Leishmania Spp mentioning
confidence: 99%
See 3 more Smart Citations